Analysis of Elementary School Students' Difficulties in Fraction Addition - Wulandari, Dwi; Amir, Mohammad Faizal (Kreano, Jurnal Matematika Kreatif-Inovatif, 2022)
This study aims to analyze the fraction addition difficulties of fourth-grade students at SDN Candinegoro No. 484. This study utilizes a qualitative approach and case study method. This study's data collection methods included tests and interviews. Data analysis consists of data reduction, data presentation, and data verification. The results of the analysis indicate that students have difficulty learning fraction addition. Students' difficulties with applying concepts, applying principles, and solving verbal problems. Through this study, it is anticipated that teachers will be able to identify the types of difficulties encountered by students when learning fraction addition. Hence, teachers can overcome the errors made by students when working on fraction addition problems. Moreover, teachers can use these guidelines when creating lesson plans to anticipate that there will be no fraction-related difficulties.Penelitian ini bertujuan untuk menganalisis kesulitan penjumlahan pecahan siswa kelas IV SDN Candinegoro No. 484. Penelitian ini menggunakan pendekatan kualitatif dan metode studi kasus. Metode pengumpulan data penelitian ini meliputi tes dan wawancara. Analisis data terdiri dari reduksi data, penyajian data, dan verifikasi data. Hasil analisis menunjukkan bahwa siswa mengalami kesulitan dalam mempelajari penjumlahan pecahan. Kesulitan yang dialami siswa pada saat menggunakan konsep, prinsip, dan menyelesaikan masalah verbal. Melalui penelitian ini diharapkan guru dapat mengidentifikasi jenis-jenis kesulitan yang dihadapi siswa ketika mempelajari penjumlahan pecahan. Dengan demikian, guru dapat mengatasi kesalahan yang dilakukan siswa saat mengerjakan soal penjumlahan pecahan. Selain itu, guru dapat menggunakan pedoman tersebut saat membuat rencana pelaksanaan pembelajaran untuk mengantisipasi agar tidak ada kesulitan terkait pecahan.